PLEASE, LISTEN! CLARIFICATIONS BY CANCELLED K-POP IDOLS AND ACTORS ON SOCIAL MEDIA - Effendi, Shifaneyra Aliya Sabella; Sujadi, Rhaina Syifa Awwalya; Widyaningsih, Desi Lutfiana (Ma Chung Press, 2025)
Abstract: This study analyzed the communication strategies used in clarification messages posted by Korean idols and actors on social media when facing canceled culture. This study used a qualitative approach, and the data used in this analysis was collected from clarification posts on official social media platforms, such as Instagram and X (Twitter), from a number of public figures in the Korean entertainment industry between 2018 and 2024. The analysis of this data was made by using Benoit's (1997) Image Repair Theory, Walton's (1993) Clarification Speech Act, and Alsharif's (2023) Emotional Appeal. This study found three types of clarification strategies that are often used by figure manufacturers in their clarification letters: (1) Apology, which is an acknowledgment of mistakes and a promise to improve behavior, (2) Explanation, to correct misinformation and provide context for what is happening, (3) Emotional Appeal, manifested through expressions of humility and acknowledgment of the feelings and difficulties of the victim to evoke sympathy from the audience. The results of the study show that clarification on social media was a complex crisis management strategy. The three strategies not only served to repair their damaged reputation, but also became a means of negotiating their close relationship with fans and showing behavior according to cultural norms in Korea, which emphasize sincerity and humility. Keywords: Cancel Culture, K-Pop, Clarification, Communication Strategy, Image Repair, Social Media, Korean Entertainment Industry.